Toxicidade de imidacloprid e carbofuran para organismos aquáticos de diferentes níveis tróficos - Américo-Pinheiro, Juliana Heloisa Pinê [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The use of pesticides can cause contamination of aquatic ecosystems and intoxicate non-target organisms. The objective was to assess the acute toxicity of imidacloprid and carbofuran insecticide to aquatic organisms belonging to different trophic levels, assess quality variables of water during rehearsals, classify insecticides on the risk of environmental poisoning for each organism, evaluate hematological and histolological changes caused by sublethal concentrations of pesticides in Oreochromis niloticus. Acute toxicity tests were performed with Daphnia magna, Lemna minor, Pomacea canaliculata and tilapia according to ABNT and OECD. Chronic toxicity tests were conducted with tilapia according to ABNT. After exposing of fishes to sublethal concentrations of pesticides for seven days, blood samples were collected for hematological analysis and organs (gill, liver, kidney and gonad) for histological evaluation. Imidacloprid is slightly toxic to D. magna and practically non-toxic to L. minor, P. canaliculata and O. niloticus. The risk of environmental poisoning of imidacloprid is down to the assessed organisms. Carbofuran is highly toxic to D. magna, highly toxic to O. niloticus and practically non-toxic to L. minor and P. canaliculata. The risks of environmental poisoning for L. minor and P. canaliculata due to contamination of water with carbofuran are classified as low. To D. magna and O. niloticus the risk varies from high to medium. The chronic sublethal exposure to insecticides tilapia change hematological parameters and causes histological changes in gill, liver, kidney and gonad. The presence of imidacloprid and carbofuran in aquatic environments may compromise the survival of non-target organisms and impair the operation of fish organs exposed. The dilution of imidacloprid and carbofuran increases the electrical conductivity of water

A utilização de agrotóxicos pode causar contaminação dos ecossistemas aquáticos e intoxicar organismos não alvos. Objetivou-se avaliar a toxicidade aguda dos inseticidas imidacloprid e carbofuran para organismos aquáticos pertencentes a diferentes níveis tróficos, avaliar variáveis de qualidade de água durante os ensaios, classificar os inseticidas quanto ao risco de intoxicação ambiental para cada organismo e avaliar alterações hematológicas e histológicas causadas por concentrações subletais dos inseticidas em Oreochromis niloticus. Ensaios de toxicidade aguda foram realizados com Daphnia magna, Lemna minor, Pomacea canaliculata e tilápia de acordo com as normas da ABNT e OECD. Ensaios de toxicidade crônica foram realizados com tilápia de acordo com a ABNT. Após a exposição dos peixes às concentrações subletais dos inseticidas por sete dias, foram coletadas amostras de sangue para análise hematológica e de órgãos (brânquia, fígado, rim e gônada) para avaliação histológica. O imidacloprid é ligeiramente tóxico para D. magna e praticamente não tóxico para L. minor, P. canaliculata e O. niloticus. O risco de intoxicação ambiental do imidacloprid é baixo para os organismos avaliados. O carbofuran é extremamente tóxico para D. magna, altamente tóxico para O. niloticus e praticamente não tóxico para L. minor e P. canaliculata. Os riscos de intoxicação ambiental para L. minor e P. canaliculata devido à contaminação da água com carbofuran classificam-se como baixo. Para D. magna e O. niloticus o risco varia de alto a médio. A exposição subletal crônica de tilápias aos inseticidas altera os parâmetros hematológicos e causa alterações histológicas em brânquia, fígado, rim e gônada. A presença de imidacloprid e carbofuran em ambientes aquáticos pode comprometer a sobrevivência de organismos não alvos e prejudicar o funcionamento dos órgãos dos peixes expostos. A diluição...
Keywords: Produtos químicos agrícolas; Tilapia (Peixe); Histologia; Toxicidade Aguda; Impacto ambiental; Histology